Ancia Zarichanska and Folk Belief in Transcarpathia: A Comparative Perspective - Korol, Vasyl; Kryvonos, Oleksandr (Ethnographica et Folkloristica Carpathica, 2025)
This study focuses on the historical figure of Ancia Zarichanska (Anna Poidyn), a spiritual mediator and charismatic healer from the Transcarpathian village of Zarichchia. Based on extensive ethnographic fieldwork (2018–2019) and qualitative interviews with local informants, the article examines the narrative construction of this woman in collective memory, as well as her magical abilities, ritual practices, and ascetic lifestyle. Her unusual behavior – including voluntary seclusion, visionary experiences, fasting, and selective social interaction - is interpreted as an expression of religious asceticism, deviant piety, and spiritual authority. Central elements such as near-death experience, rebirth motifs, and prophetic healing are analyzed in comparison with European folk healers, visionary figures, and shamanic initiation processes. Zarichanska’s case demonstrates how spiritual legitimacy can be established outside institutional religion. Particular attention is paid to the cultural logic underlying the attribution of mystical authority, the emergence of local rituals such as “Hercna Wednesday,” and the ritual veneration of her grave as a site of popular devotion. This study contributes to the ethnology of folk belief by showing how collective memory, oral tradition, demonological narratives, and religious-magical practices interweave to shape local forms of “folk sainthood.” The figure of Zarichanska is presented as a paradigmatic example of trans-cultural patterns of non-institutional spirituality, which fulfill identity-forming functions, especially in times of social transformation.